2021
DOI: 10.1109/access.2020.3036423
|View full text |Cite
|
Sign up to set email alerts
|

Robust Cubature Kalman Filter for SINS/GPS Integrated Navigation Systems With Unknown Noise Statistics

Abstract: Date of publication xxxx 00, 0000, date of current version xxxx 00, 0000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Referring to [12] for the equation simplification and derivation process, the measurement update can be given by:…”
Section: Robust Kalman Filter Based On MCCmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to [12] for the equation simplification and derivation process, the measurement update can be given by:…”
Section: Robust Kalman Filter Based On MCCmentioning
confidence: 99%
“…However, these methods still assign some weight to invalid measurements. Using a maximum correlation entropy improvement, the Kalman filter can be improved to address non-Gaussian noises [11][12][13], and the weights of measurement information are updated in real time. The Kalman filter obtains better performance when the non-Gaussian noises are suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…The SINS solution value is corrected using the estimated state feedback, the CKF filtering is implemented using the calculated variance parameter, and, finally, the forecast value is updated. The predicted value is estimated and updated, as well as the subsequent sample point during this processing [29]. The system also outputs the filtered navigation parameter data at the same time.…”
Section: Algorithm Test Planmentioning
confidence: 99%
“…Chen proposed an adaptive extended Kalman filter (EKF) algorithm in the literature [19] to eliminate the improper selection of noise covariance, and experiments show that the algorithm effectively improves the positioning accuracy of INS/GNSS. Feng proposed a new robust volume Kalman filter based on adaptive information entropy theory in the literature [20], which effectively suppresses the process uncertainty and non-Gaussian measurement noise, and experiments show that the filter has higher estimation accuracy and stronger robustness. Sun proposed a new measurement noise covariance update scheme in the literature [21], which was tested on a integrated GNSS/inertial measurement unit (IMU) navigation system in urban areas using adaptive metrics generated from pseudorange error prediction results, and the experiments showed that the accuracy of 3D positioning was effectively improved.…”
Section: Introductionmentioning
confidence: 99%